A Tetraphenylethylene Core‐Based 3D Structure Small Molecular Acceptor Enabling Efficient Non‐Fullerene Organic Solar Cells. (27th November 2014) - Liu, Yuhang; Mu, Cheng; Jiang, Kui; Zhao, Jingbo; Li, Yunke; Zhang, Lu; Li, Zhengke; Lai, Joshua Yuk Lin; Hu, Huawei; Ma, Tingxuan; Hu, Rongrong; Yu, Demei; et al.
<x xml:space="preserve">Abstract</x> A tetraphenylethylene core‐based small molecular acceptor with a unique 3D molecular structure is developed. Bulk‐heterojunction blend films with a small feature size (≈20 nm) are obtained, which lead to non‐fullerene organic solar cells (OSCs) with 5.5% power conversion efficiency. The work provides a new molecular design approach to efficient non‐fullerene OSCs based on 3D‐structured small‐molecule acceptors. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>